MONEY ETHICS MODERATION, ORGANIZATIONAL COMMITMENT AND ORGANIZATION ETHICAL CULTURE ON THE EFFECT OF BUDGET PARTICIPATION ON BUDGETARY SLACK - Jati I K.; Widhiyani N.L.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
Budgetary slack is suspected to have occurred at the Office of Information and Communication Technology Management and State Property (KPTIK and BMN work unit), the Ministry of Finance of the Republic of Indonesia, which is possibly caused by dysfunctional behavior in budget participation. Raudhiah et al. 2013 emphasized that budgetary slack is used to make budget targets easier to achieve by manipulating the budget. However, the empirical research that has been conducted by several researchers shows inconsistent results which indicate a moderating role for contingency factors. The purpose of this study is to confirm the effect of budget participation on budgetary slack. The study population was a registered tax consultant and worked in the KPTIK and BMN (Ministry of Finance) work unit. The sampling technique was purposive sampling. Furthermore, data was collected through primary data sources using a questionnaire from previous researchers which was modified and fulfilled the validity and reliability test requirements of the instrument. Then, the data collected were tabulated and several tests and analyzes were carried out, namely: 1) classical assumption test to ensure fulfillment of the requirements for Best Linear Unbiased Estimator (BLUE), 2) Descriptive Static Analysis, 3) model feasibility test (F test), 4) analysis of the coefficient of determination (Adj. R2), and 5) test the research hypothesis (t-test). The MRA test results found that budgetary participation has a positive and significant effect on budgetary slack. Money ethics does not significantly increase the positive effect of budget participation on budgetary slack. Organizational commitment weakens the positive effect of budget participation on budgetary slack significantly . The ethical culture of the organization weakens significantly the positive influence of budget participation on budgetary slack.